IMPLICATION OF LOCAL RHEOLOGY STRUCTURE IN POSTSEISMIC DEFORMATION ANALYSIS: A CASE STUDY OF THE 2018 LOMBOK, INDONESIA EARTHQUAKE - Nurrohmah, Lila
The postseismic deformation of the 2018 Lombok earthquake was investigated using Global Navigation Satellite System (GNSS) data. The GNSS data employed in this study captured the deformation pattern observed a few days after the 2018 Lombok earthquake sequence. Two physical mechanisms of postseismic deformation (afterslip and viscoelastic relaxation) were analyzed in this research. Viscoelastic relaxation was calculated using Maxwell viscoelastic model for layered earth model. The layered earth model combines a local velocity model for depths up to 310 km with the global velocity model AK135 for deeper depths. The afterslip distribution along the fault plane was modelled using geodetic inversion method employing Akaike's Bayesian Information Criterion (ABIC). For the afterslip calculation, a fault plane size of 100 × 37 km was utilized, with the western segment sized 30 × 37 km, the central segment sized 40 × 37 km, and the eastern segment 30 × 37 km. Each fault’s segment was subdivided into smaller patches, size of 10 × 7,4 km. The strike of western fault segment was 79°, while the central and eastern segments had strike of 90°and 101°, respectively. A rake of 93°also applied for all sub-faults. The optimum rheological model revealed a 35 km thick elastic layer with the Maxwell viscosity of the asthenosphere is 2.0 × 1017 Pa s. The relatively thin elastic layer and less viscous asthenosphere are consistent with the study area that is located in the back-arc region.